Lateralized behaviour of a non-social cichlid fish (Amatitlania nigrofasciata) in a social and a non-social environment - Moscicki, Michele K.; Reddon, Adam R.; Hurd, Peter L. (My University, 2011)
Cerebral lateralization, the partitioning of cognitive function preferentially into one hemisphere of the brain, is a trait ubiquitous among vertebrates. Some species exhibit population level lateralization, where the pattern of cerebral lateralization is the same for most members of that species; however, other species show only individual level lateralization, where each member of the species has a unique pattern of lateralized brain function. The pattern of cerebral lateralization within a population and an individual has been shown to differ based on the stimulus being processed. It has been hypothesized that sociality within a species, such as shoaling behaviour in fish, may have led to the development and persistence of population level lateralization. Here we assessed cerebral lateralization in convict cichlids ( Amatitlania nigrofasciata), a species that does not shoal as adults but that shoals briefly as juveniles. We show that both male and female convict cichlids display population level lateralization when in a solitary environment but only females show population level lateralization when in a perceived social environment. We also show that the pattern of lateralization differs between these two tasks and that strength of lateralization in one task is not predictive of strength of lateralization in the other task.
Keywords: Amatitlania nigrofasciatus; cerebral lateralization; convict cichlids